Higher Education and Social Justice The Transformative Potential of University Teaching and the Power of Educational Paradox - Rowan, Leonie (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
XVII, 141 p. 5 illus., 4 illus. in color.